Pengaruh Kinerja Keuangan, Struktur Kepemilikan dan Diversifikasi Produk terhadap Pengungkapan HRA pada Perusahaan LQ45 - I Nyoman Adi Darmayasa; Putu Sukma Kurniawan (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aims to examine the effect of financial performance, ownership structure, and product diversification on the disclosure of human resource accounting (HRA) on companies listed in the LQ45 index for the period 2014 - 2018. Disclosure of HRA needs to be considered because it will reflect how companies use resources specifically human resources (HR) owned. This research uses quantitative methods. The sampling technique in this study used purposive sampling by adjusting to certain criteria to obtain 26 samples. Supporting data can be obtained from the official website of the Indonesia Stock Exchange (IDX) with a period of 5 years. In analyzing research data, multiple linear regression was used with the help of the IBM SPSS version 24 program. The results of this study stated that financial performance, ownership structure, and product diversification partially had a positive effect on HRA disclosure. Good financial performance will cause companies to disclose more HRA. A high ownership structure will increase the controlling function so that the disclosure of HRA will be more numerous. With so many product diversifications, companies tend to disclose HRA in full.